Online purchase determinants of loyalty: the mediating effect of satisfaction in tourism - Pereira, H.; Salgueiro, M. F.; Rita, P. (Journal of Retailing and Consumer Services, 2016)
The purpose of this research is to investigate the impact of four online purchase determinants (website image, routine, website knowledge and innovativeness) on customer loyalty and the mediating effect of customer satisfaction within the context of e-commerce. The research model is tested using data collected from 3188 regular buyers of the national leader in the sector being studied. The statistical analyses were conducted within the Structural Equation Modeling framework. Results show that there is a complete mediating effect of e-customer satisfaction in the relationship between three online purchase determinants (website image, online routine and website knowledge) and e-customer loyalty. The research results provide an important insight into how e-companies can pursuit and use delight to highlight customers' loyalty. These results allow for a better understanding of customer specificities, with practical actions aimed at their real needs and expectations.